It’s in your blood: understanding memory loss when blood vessels malfunction - Padgett, Matthew (2024)
The bilateral carotid artery stenosis model, (BCAS), is a popular method in which to model vascular cognitive impairment in the mouse. This model has gained in popularity due to reports of selective white matter deficits accompanying cognitive decline. However, physiological and behavioural deficits have not always been replicated across different research groups, suggesting high levels of variability in the model. The overall aim of this thesis was to assess cognitive decline in the BCAS model in the lab and across the literature, as well as assessing biological changes to the visual system and cerebral white matter.